Presurgical assessments (Assessments vor Operationen) - Kahlmeyer, A.; Goebell, Peter; Wullich, Bernd (Urologe, 2019)
For the estimation of perioperative risks and mortality in the context of radical urological tumor surgery in elderly patients, the guidelines meanwhile require the use of geriatric assessments. The aim of this work is therefore to explain frequently used geriatric assessments and to give an overview of their predictive significance in radical urological tumor surgery. Comprehensive geriatric assessments provide a good description of the patient’s state of health, but are hardly feasible in clinical routine due to their complexity. It is more reasonable to use screening tools with subsequent targeted examination of high-risk patients. Special tools allow the standardized assessment of functional status, mobility, cognition, mood, nutrition, frailty, comorbidities and polypharmacy and have different prognostic significance. Evidence on the predictive value of assessments prior to radical urological tumor surgery is mainly described for the systematic classification of comorbidities. In cystectomy, the Charlson Comorbidity Index (CCI) and the American Society of Anesthesiologists (ASA) score allow an estimation of the risk of complications and mortality. The focus of assessments prior to prostatectomy is to identify patients with sufficient life expectancy to benefit from radical surgery. CCI and ASA scores as well as the Eastern Co-operative Oncology Group (ECOG) score can help to assess the risk of perioperative complications in kidney tumor surgery.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cognition; Cystectomy; Geriatric Assessments; Nephrectomy; Prostatectomy